Six microlensing planets detected via sub-day signals during the 2023–2024 season - Han C; Lee C-U; Udalski A; Bond IA; Albrow MD; Chung S-J; Gould A; Jung YK; Hwang K-H; Ryu Y-H; Shvartzvald Y; Shin I-G; et al. (EDP Sciences on behalf of The European Southern Observatory (Ulis, France), 2025)
Aims. We present analyses of six microlensing events: KMT-2023-BLG-0548, KMT-2023-BLG-0830, KMT-2023-BLG-0949, KMT-2024-BLG-1281, KMT-2024-BLG-2059, and KMT-2024-BLG-2242. These were identified in KMTNet data from the 2023–2024 seasons, selected for exhibiting anomalies shorter than one day – potential signatures of low-mass planetary companions. Motivated by this, we conducted detailed investigations to characterize the nature of the observed perturbations. Methods. Detailed modeling of the light curves reveals that the anomalies in all six events are caused by planetary companions to the lenses. The brief durations of the anomalies are attributed to various factors: a low planet-to-host mass ratio (KMT-2024-BLG-2059, KMT-2024-BLG-2242), a wide planet-host separation (KMT-2023-BLG-0548), small and elongated caustics restricting the source’s interaction region (KMT-2023-BLG-0830, KMT-2024-BLG-1281), and a partial caustic crossing (KMT-2023-BLG-0949). Results. We estimated the physical parameters of the lens systems using Bayesian analysis. For KMT-2023-BLG-0548, the posterior distribution of the lens mass shows two distinct peaks: a low-mass solution indicating a sub-Jovian planet orbiting an M dwarf in the Galactic disk, and a high-mass solution suggesting a super-Jovian planet around a K-type dwarf in the bulge. KMT-2023-BLG-0830 hosts a Neptune-mass planet orbiting an M dwarf in the Galactic bulge. KMT-2023-BLG-0949 involves a super-Jovian planet orbiting a ∼0.5 M☉ host located at ∼6 kpc. KMT-2024-BLG-2059Lb is a super-Earth with a mass about seven times that of Earth, orbiting an early M dwarf of ∼0.5 M☉. KMT-2024-BLG-1281L hosts a planet slightly more massive than Neptune, orbiting an M dwarf of ∼0.3 M☉. The short timescale and small angular Einstein radius of KMT-2024-BLG-2242 suggest a ∼0.07 M☉ primary, likely a brown dwarf, with a planet of Uranus- or Neptune-like mass.
Keywords: gravitational lensing; micro / planets and satellites; detection